An assessment of the BSMT apprenticeship program by deck cadets of John B. Lacson Foundation Maritime University-Arevalo, Inc. - Basbas, Bernabe Adelante (University of the Philippines in the VIsayas, 2011)
This study assessed the level of satisfactoriness and adequacy of the different aspects of the BSMT Apprenticeship Program among the Deck Cadets of John B. Lacson foundation Maritime University (JBLFMU)-Arevalo, Inc. Respondents of this study were fifty-five (55) company-sponsored scholars, who went onboard training vessels during the School Year 2010-2011, and eventually enrolled in the regular and special program classes during the School Year 2011-2012. Using the Survey Questionnaire of the Seamanship and Navigation Apprenticeship Program, ratings were gathered on three aspects of the program : 1)Satisfactoriness of benefits, support and opportunities ; 2) Satisfactoriness of the quality of physical conditions and social-psychological atmosphere, and 3) the Adequacy of the training program itself. The instrument which consists of Likert-type items and a scale of 1-6 representing levels of satisfactoriness/adequacy was validated with an independent group of respondents and experts. Means (M) and standard deviations (SD) in the subscales were computed for each group of students classified accroding to type of class, type of vessel, and nationality of principal. On the basis of the findings of this study, it is recommended that JBLFMU officials and principals of vessels involve in apprenticeship conduct a dialogue/conference to discuss issues obtaining from the following areas of concern : 1) Improvement of the benefits, support and opportunities, particularly family support and opportunities for socialization. 2) Improvement of physical conditions particularly health and sanitation and cleanliness. 3)Enhancement of communication and respect for individual differences, with effort to elminate communication barriers and encourage social interaction to foster camaraderie and fellowship to reduce discrimination. 4) Motivational support and recognition of work performance onboard to develop teamwork and boost self-esteem. 5) Conduct of training on caring for persons onboard at hte operational level to give emphasis and attention fostering healthy and responsible relationships. 6) Provision of experiences on hands-on navigation at the operational level to deck cadets who will become future officers. 7) Provision of support for attitude development particularly perseverance, equality, godliness and excellence in keeping with Institution's core values and goal to develop well-rounded individuals. 8) A broader in scope and a more comprehensive research should be made pertaining to the apprenticeship program.